Academic tutorship and personal tutorship student’s postgraduate with anxiety - Abrego Ramírez, Adrián (Gaceta Médica de Caracas, 2021)
Anxiety in university students is a problem that has a high prevalence, one of the factors that can influence is education, although it also needs to make use of different resources to improve care This activity has to be done by considering quality, maintaining good and appropriate didactic practice, revising general education results, and by carrying on tutorship, a supporting alternative.